2021
DOI: 10.21500/22563202.4574
|View full text |Cite
|
Sign up to set email alerts
|

Investigación en publicidad política: un análisis bibliométrico

Abstract: La publicidad política (PP) se ha configurado en un campo de alto interés para los científicos sociales a través del tiempo. El propósito de este documento es analizar la literatura desarrollada alrededor de la PP, identificando la tendencia de crecimiento en el tiempo, autores relevantes, regiones donde se ha estudiado mayoritariamente el concepto, características fundamentales de la PP y finalmente, líneas futuras de investigación. En la investigación se emplea un análisis bibliométrico de 295 manuscritos ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…In addition, carrying out a study and bibliometric analysis of the identified documents will allow the evolution and trend of the number of publications in relation to a thematic line to be understood [ 37 ]. In the same way, a series of elements or factors are identified, providing knowledge and favoring the understanding of the contents [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, carrying out a study and bibliometric analysis of the identified documents will allow the evolution and trend of the number of publications in relation to a thematic line to be understood [ 37 ]. In the same way, a series of elements or factors are identified, providing knowledge and favoring the understanding of the contents [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Por otra parte, el propio término tiene connotaciones cada vez más desfavorables: ¿acaso no se lee, según han dejado escrito los redactores del célebre Mercator, que "la publicidad es una información seleccionada, frecuentemente mutilada y por tanto tendenciosa"? La publicidad pertenece, en realidad, a la génesis de la comunicación (Arango, Ceballos, & Osorio, 2020), exactamente como su equivalente en el plano de la comunicación política, la propaganda. Ésta, generalmente, no era más que la adaptación a la comunicación gubernamental de la comunicación publicitaria "a la antigua": una comunicación unidireccional que intenta imponer una opinión.…”
Section: Comunicación Publicidad Y Propagandaunclassified
“…Taking as a reference the classification established by Montero and León [42], the present study falls within the "Ex post facto retrospective" studies because bibliometric research related to the biomechanical study in gymnastics is the focus of this study. A bibliometric review will allow us to understand the status of a thematic line about different factors and variables [43] and to establish future lines of research.…”
Section: Designmentioning
confidence: 99%